William Penn : politics and conscience - Dunn, Mary Maples (Princeton legacy library., 2015)
This is a concise, fluently presented examination of the relation between William Penn's religious convictions and his political behavior, from his years as an active young convert to the Quaker cause to his later years as governor of Pennsylvania. Although not a full biographical treatment of William Penn, the study presents new insights into Penn's life because it is based on many ignored but important pamphlets that Penn wrote. The young William Penn took a leading role in the Quaker fight for the right of free assembly, the right of free speech, and freedom of conscience. However, when faced with governing a booming colony, these very principles and convictions had to be modified in order to maintain his and the Friends' control of Pennsylvania. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.